Data-Driven Zero Trust Key Algorithm - Liu, Zhiwei; Li, Xiaoyu; Mu, Dejun (Wireless communications and mobile computing, 2022)
In today’s information society, network security is a crucial issue. Network security technology is changing as a result of the development of emerging technologies such as big data, cloud computing, and artificial intelligence. Data-driven (DD) security has emerged as a new network security technology development direction. The key technologies for DD network security are discussed in depth in this paper. A data security protection system is designed from the perspective of ZT, based on advanced security concepts and technologies developed by ZT, as well as a foreign data security governance framework. The number of alarms generated per hour is counted, removal rules are defined, and real-time rule matching is performed to eliminate false alarms based on different combinations of attributes. By analyzing the security data generation rules and internal relations, a security aggregation method can reduce redundant data and improve alarm quality.